Analysis of Foreign Grants for Forestry Development Before and Amid the Covid-19 Pandemic - Susanto, Wahyudi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
The decline in economic growth in Indonesia also has an impact on the forestry sector and puts pressure on the performance of the forestry sector. Innovations and breakthroughs are needed to accelerate the pace of forestry development that is adaptive, credible, competitive, and transparent, especially in the aspect of financing development in the forestry sector. One alternative to development funding in the forestry sector is through foreign grants. Therefore, a study is needed to analyze the impact of the foreign grant project on forestry development in Indonesia, especially during and after the Covid-19 pandemic. The data collection in this study was carried out by literature studies, field observations, organizing coordination meetings and focus group discussions (FGD) and then analyzed using quantitative descriptive methods using a quadrant analysis approach. The results of this study indicate that: 1) project performance from the budget side has not shown consistent results compared to the plan; 2) foreign grant project support in the forestry sector has a strategic role in the development funding policy framework as well as supporting national development targets and regional development at the project site, however, foreign grant project support has not been fully aligned with the national development plan; 3) the Covid-19 pandemic has become an obstacle in implementing foreign grants, especially at the site level; 4) the implementation of foreign grant projects before and during the Covid-19 pandemic had a positive impact on forestry development in Indonesia; dan 5) the benefits of foreign grant project activities get a positive response and are well received by the community. There is still a need to improve the quality of performance in the management of foreign grants, both in terms of planning and program implementation. This is needed to achieve national priority development targets, support economic recovery and improve forest management at the post-Covid-19 pandemic in Indonesia.